Metabolic engineering of Corynebacterium glutamicum for efficient production of 5‐aminolevulinic acid. Issue 6 (9th December 2015) - Feng, Lili; Zhang, Ya; Fu, Jing; Mao, Yufeng; Chen, Tao; Zhao, Xueming; Wang, Zhiwen
ABSTRACT: 5‐Aminolevulinic acid (5‐ALA) has recently attracted attention for its potential applications in the fields of medicine and agriculture. In this study, Corynebacterium glutamicum was firstly engineered for 5‐ALA production via the C4 pathway. HemA encoding 5‐aminolevulinic acid synthase from Rhodobacter sphaeroides was codon optimized and expressed in C. glutamicum ATCC13032, resulting in accumulation of 5‐ALA. Deletion of all known genes responsible for the formation of acetate and lactate further enhanced production of 5‐ALA. Overexpression of ppc gene encoding phoenolpyruvate carboxylase resulted in an accumulation of 5‐ALA up to 2.06 ± 0.05 g/L. Furthermore, deletion of high‐molecular‐weight penicillin‐binding proteins (HMW‐PBPs) genes pbp1a, pbp1b, and pbp2b led to an increase in 5‐ALA production of 13.53%, 29.47%, and 22.22%, respectively. Finally, 5‐ALA production was enhanced to 3.14 ± 0.02 g/L in shake flask by heterologously expressing rhtA encoding threonine/homoserine exporter, and 86.77% of supplemented glycine was channeled toward 5‐ALA production in shake flask. The engineered C. glutamicum ALA7 strain produced 7.53 g/L 5‐ALA in a 5 L bioreactor. This study demonstrated the potential utility of C. glutamicum as a platform for metabolic production of 5‐ALA. Change of cell permeability by metabolic engineering HMW‐PBPs may provide a new strategy for biochemicals production in Corynebacterium glutamicum . Biotechnol. Bioeng. 2016;113: 1284–1293. © 2015 Wiley Periodicals, Inc. Abstract : Figure 1 Metabolic pathways associated with 5‐ALA biosynthesis in Corynebacterium glutamicum and the metabolic engineering strategies for aerobic 5‐ALA overproduction.